The genus Contracaecum Raillet & Henry (Nematoda: Anisakidae): host and geographical distribution on Neotropical and Antarctic species - Garbin, Lucas; Diaz, Julia Inés; Servian, Andrea; Fusaro, Bruno; Navone, Graciela Teresa (Zootaxa)
Nematodes of the genus Contracaecum Raillet & Henry, 1912 (Anisakidae, Contracaecinae) have a worldwide distribution. The taxonomy of the genus Contracaecum is well-known nowadays due to several morphometric studies, scanning electron microscopy, and molecular biology. The aim of this work was to review, clarify, and summarize the valid species of the genus Contracaecum parasitizing piscivorous sea birds and mammals from both the Neotropical and Antarctic regions reviewing all scientific available papers and electronic searching data up to date. A checklist on Neotropical and Antarctic Contracaecum spp. was organized through a revision of scientific papers and original descriptions. The systematic online search and the most updated papers were obtained through SCOPUS, Google Scholar, PubMed, Medline, World Register of Marine Species, etc. We provide information about hosts, Neotropical and Antarctic localities where worms were collected, references, molecular markers, and Genbank accession numbers. Twenty-five Neotropical and Antarctic Contracaecum species have been recorded up to date and checked out as valid ones according to the most updated data. Twenty-one species parasitize exclusively fish-eating birds, two species were reported only on marine mammals, and the other two parasitize both sea birds and mammals. A total of 20 Contracaecum species are exclusively reported for the Neotropical region, three only for Antarctic hosts, and two species were reported parasitizing both Neotropical and Antarctic hosts. Several Contracaecum species (10) have been corroborated by molecular analysis of different genetic markers. After reviewing all morphological descriptions of the Contracaecum species, and despite most of them have been characterized only by morphometric methods, we are convinced that all species listed in this work correspond to good and valid Contracaecum Neotropical and Antarctic species. Present results indicate that more taxonomic and molecular studies are needed to advance the understanding of ...